PENGEMBANGAN PERANGKAT PEMBELAJARAN BERBASIS DIGITAL DENGAN APLIKASI ARTICULATE STORYLINE UNTUK MELATIH LITERASI SAINS - Witri Saidini mukti Melani; Hanum Mukti Rahayu; Ari Sunandar (Pedagogi: Jurnal Ilmu Pendidikan, 2022)
This study aims to develop digital-based learning tools to train scientific literacy. The method used is the Research and Development development method. Sugiono's research model, however, usage trials, product revisions, and mass production were not carried out. The results of the validity interpretation research show that the learning device development product developed consists of language aspects 74%, material 85%, media 74%, while the practicality test obtains an average value of 77%. Interpretation of the results of student responses can be categorized as good with a value of 63% so that the learning device is said to be suitable for use by educators and students in the learning process.